PERBANDINGAN METODE REGRESI LOGISTIK BINER DAN METODE BACKPROPAGATION DALAM MENENTUKAN MODEL TERBAIK UNTUK KLASIFIKASI PENGGUNA PROGRAM KELUARGA BERENCANA - Muhammad Mujahid; Hasbi Yasin; Moch. Abdul Mukid (Jurnal Gaussian, 2016)
Indonesia is one of the highest population density in the world has high birth level. One of the regulation to get the population density lower than before that is used by Government is Family Planning Program. On the reality, not all of the productive age join this program. The method is Binary Logistic Regression and Backpropagation. The predictor variables that is researched are husband’s age, wife’s age, age of the last child, count of children, husband’s education, wife’s education, husband’s job, wife’s job and the level of family prosperity. The aim of the research is to compare the classification accuracy between Binary Logistic Regression and Backpropagation. The result of the research by binary logistic regression method, shows the variables that affect the status of KB user is age of the last child and wife’s education with the classification accuracy are 66.98%, and the classification accuracy of Backpropagation are 67,30%. The conclution based on the research that is the Backpropagation is better than Binary Logistic Regression when classification the status of KB user in Semarang on March 2013 until Januari 2014. Keywords :   Binary Logistic Regression, Backpropagation, Keluarga Berencana, Classification